Women's and care providers' perspectives of quality prenatal care: a qualitative descriptive study - Sword Wendy; Heaman Maureen I; Brooks Sandy; Tough Suzanne; Janssen Patricia A; Young David; Kingston Dawn; Helewa Michael E; Akhtar-Danesh Noori; Hutton Eileen (BMC, 2012)
Abstract Background Much attention has been given to the adequacy of prenatal care use in promoting healthy outcomes for women and their infants. Adequacy of use takes into account the timing of initiation of prenatal care and the number of visits. However, there is emerging evidence that the quality of prenatal care may be more important than adequacy of use. The purpose of our study was to explore women's and care providers' perspectives of quality prenatal care to inform the development of items for a new instrument, the Quality of Prenatal Care Questionnaire. We report on the derivation of themes resulting from this first step of questionnaire development. Methods A qualitative descriptive approach was used. Semi-structured interviews were conducted with 40 pregnant women and 40 prenatal care providers recruited from five urban centres across Canada. Data were analyzed using inductive open and then pattern coding. The final step of analysis used a deductive approach to assign the emergent themes to broader categories reflective of the study's conceptual framework. Results The three main categories informed by Donabedian's model of quality health care were structure of care, clinical care processes, and interpersonal care processes. Structure of care themes included access, physical setting, and staff and care provider characteristics. Themes under clinical care processes were health promotion and illness prevention, screening and assessment, information sharing, continuity of care, non-medicalization of pregnancy, and women-centredness. Interpersonal care processes themes were respectful attitude, emotional support, approachable interaction style, and taking time. A recurrent theme woven throughout the data reflected the importance of a meaningful relationship between a woman and her prenatal care provider that was characterized by trust. Conclusions While certain aspects of structure of care were identified as being key dimensions of quality prenatal care, clinical and interpersonal care processes emerged as being most essential to quality care. These processes are important as they have a role in mitigating adverse outcomes, promoting involvement of women in their own care, and keeping women engaged in care. The findings suggest key considerations for the planning, delivery, and evaluation of prenatal care. Most notably, care should be woman-centred and embrace shared decision making as an essential element.